Implementasi Sistem Manajemen Logistik Berbasis Website Menggunakan PHP dan MySQL Studi Kasus BPBD Kota Cimahi - Intania, Fenty; Rusghana, Fadzar (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The process of managing logistics storage at BPBD Cimahi is still done conventionally. Activities carried out for the management of goods data use manual recording that has not been integrated with the system. resulting in the process of managing logistics goods being not well structured and taking quite a long time. Logistics management information system (SiLogis) can help solve these problems. SiLogis can simplify the recording process so that logistics data can be stored properly, while the system can display all developments from data logistics through diagrams and graphs to simplify the manufacturing process. The SiLogis design process uses object-oriented methods with UML diagrams to create a system model and create a system view design (wireframe). After the system design process is made, then the author implements the system using HTML Bootstrap technology for the front view, PHP Codeigniter to create system functionality, and MySql database for data storage.